Electronic transport properties of pnictogen-substituted skutterudites with alkaline-earth fillers. Issue 1680 (21st August 2014) - Bang, Semi; Li, An; Wee, Dae Hyun; Fornari, Marco; Kozinsky, Boris
ABSTRACT: The materials class of skutterudites is one of the promising thermoelectric materials due to its decent electronic properties and cage-like structural feature that can be filled with guest atoms. First principles calculations have been performed in order to investigate electronic band structures and related transport properties of pnictogen-substitued skutterudites filled with alkaline-earth elements (Mx Co4 A6 Te6 where M=Ca, Sr, or Ba, A=Ge or Sn, and x=0.5 or 1). The Seebeck coefficient and the power factor, which are electronic transport properties related to thermoelectricity, are computed by using the Boltzmann transport formalism within the constant-relaxation-time-approximation. The results are compared against the corresponding properties of the unfilled pnictogen-substitued ternary skutterudites (CoA1.5 Te1.5 ) to identify the effects of filling, based on which the potential of filled pnictogen-substituted skutterudites for thermoelectric applications is evaluated. The possible changes in the ionic character of the interatomic bonding, which was suspected to be an important scattering source, are probed by analyzing the projected density of states.